The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1002/1097-0290(20010220)72:4<475::aid-bit1009>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Siloxane-based biocatalytic films and paints for use as reactive coatings

Abstract: We have developed a new methodology for preparing films and paints suitable for use as biocatalytic coatings. The hydrolytic enzymes pronase and α‐chymotrypsin were immobilized by either sol‐gel entrapment or by covalent attachment into a polydimethylsiloxane (PDMS) matrix and cast into thin films or incorporated into an oil‐based paint formulation. All of the coatings retained enzymatic activity and adhered to several different materials. The enzymatic films and paints also exhibited higher thermostability th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 30 publications
3
46
0
Order By: Relevance
“…In recent years enzymes have found widespread use in decontamination of waste streams (Lejeune et al, 1998). Kim et al (2001) and Asuri et al (2007) incorporated enzymes into a variety of different matrices to create self-cleaning dense surfaces that resist protein adsorption. These active proteolytic enzymes attached on surfaces could break down protein foulants, and the fragments can be subsequently removed through a simple water flashing operation.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years enzymes have found widespread use in decontamination of waste streams (Lejeune et al, 1998). Kim et al (2001) and Asuri et al (2007) incorporated enzymes into a variety of different matrices to create self-cleaning dense surfaces that resist protein adsorption. These active proteolytic enzymes attached on surfaces could break down protein foulants, and the fragments can be subsequently removed through a simple water flashing operation.…”
Section: Introductionmentioning
confidence: 99%
“…Many types of enzymes, such as oxidoreductases, transferases, hydrolase, lyase, isomerase, and ligase, have been reported to have antifouling capabilities [25,58,[97][98][99][100][101][102][103][104][105][106]. From the perspective of enzymatic antifouling technology, biofouling problems are caused by the formation and reproduction of biofilms, and the adhesion of spores and larvae of macroorganisms.…”
Section: Biological Methodsmentioning
confidence: 99%
“…An interesting feature about enzymes is their ready decomposition in the marine environment to CO 2 and H 2 O by the action of microorganisms [28]. Some studies have reported the use of enzymes as antifouling agent in coatings [33,34], even though the great variability in matrix paints, water conditions and enzyme stability make the practical application of these formulations to real situations difficult [28]. Kristensen et al [33] used glucoamylase and hexose to produce an antifouling coating with good efficiency for up 97 days of immersion in the North Sea.…”
Section: Introductionmentioning
confidence: 99%
“…Kristensen et al [33] used glucoamylase and hexose to produce an antifouling coating with good efficiency for up 97 days of immersion in the North Sea. Kim et al used pronase and α-chymotrypsin together with poly(dimethylsiloxane), reporting a reduction in protein adsorption [34].…”
Section: Introductionmentioning
confidence: 99%